Effect of an Educational Video in Reducing Anxiety Related to Electroconvulsive Therapy - Termpornlerd, Nutchaphol; Waleeprakhon, Punjaporn (Journal of the Psychiatric Association of Thailand, 2020)
Objectives : To study the effects of the electroconvulsive therapy (ECT) educational video in reducing anxiety related to electroconvulsive therapy. Methods : A randomized control trial was conducted in both new patients with received ECT and their relatives in the Department of Psychiatry, Ramathibodi Hospital from July 2019 to October 2019. The Amsterdam Pre-operational Anxiety and Information Scale (APAIS) (Thai edition) was used to measure any differences in the anxiety levels between those who watched the ECT educational video additional during routine practice, and those who only received routine practice in 3 different sessions; namely, the pre-study, post-intervention and post-acute ECT courses. Results : The addition of watching the ECT educational video during routine practice (n = 11) statistically and significantly decreases the score of all statements in APAIS when compared with the baseline (n = 10) in both post-intervention and post-acute ECT courses.The median score of APAIS in experimental group decreases from 18 points at pre-study to 10 points at post-intervention and to 6 points at post-acute ECT courses compares to control group which has 19.5, 18.5 and 12 points in these three different sessions respectively. Conclusion : Watching the ECT educational video before the first ECT session could help in reducing the anxiety level of both new ECT patients and their relatives.